2008
DOI: 10.1115/1.2749297
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of End Wall Boundary Layer Removal on Highly Loaded Axial Compressor Blade Rows

Abstract: This paper presents results of numerical investigations carried out to explore the benefit of end wall boundary layer removal from critical regions of highly loaded axial compressor blade rows. At the loading level of modern aero engine compressors, the performance is primarily determined by three-dimensional (3D) flow phenomena occurring in the end wall regions. Three-dimensional Navier–Stokes simulations were conducted on both a rotor and a stator test case in order to evaluate the basic effects and the prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…In other words, the numerical calculation can approximately reproduce the experimental results, and the discrepancy is small enough to be ignored. Therefore, the 8 compressor simulation without bleeding can be used as the baseline to study the influence of bleeding rates on the compressor overall performance at different rotation speeds by the numerical simulation.…”
Section: Analysis On the Reliability Of Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the numerical calculation can approximately reproduce the experimental results, and the discrepancy is small enough to be ignored. Therefore, the 8 compressor simulation without bleeding can be used as the baseline to study the influence of bleeding rates on the compressor overall performance at different rotation speeds by the numerical simulation.…”
Section: Analysis On the Reliability Of Numerical Simulationmentioning
confidence: 99%
“…Its intensity and range largely depended on the rate and bleeding location. By analyzing the loss and the performance of compressor after the end wall boundary layer removal, Gummer (8,9) found that the bleeding can effectively reduce the reverse-flow along the casing and blockage and loss in local region. All these previous studies have shown that it is very likely to improve compressor performance by studying air system bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…So far the studies about suction mainly concentrate on the control of the boundary layer separation on the blade SS (Song et al 2006;Guo et al 2010;Shi et al 2015b) or the three-dimensional (3D) separation in the hub corner (Sachdeva et al 2011;Pönick et al 2013;Guo et al 2008;Marsan et al 2015). Apart from some researches about the effects of bleeding system on the compressor performance (Leishman et al 2007a(Leishman et al , 2007b(Leishman et al , 2007cGrimshaw et al 2015Grimshaw et al , 2016, there are only several investigations of suction technique on the control of TLF to improve the compressor performance and stability (Gümmer et al 2008;Dobrzynski et al 2008;Shi et al 2015a). It is found that the flow fields in the tip region and operating range can be improved by the suction on the casing.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that passive flow control using vortex generators can reduce total pressure losses by affecting the corner separation at the crossing of the wall and blade [2,3]. It was reported also that active flow control using blowing, suction or synthetic jets can decrease greatly the total pressure losses by removing the corner separation [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%